Analysis on the Effectiveness of the Input in Household Waste Classification of Residents—Taking S City in China as an Example - Yangyang Zhang (MDPI AG, 2021)
S city in China has implemented a waste classification system and constructed a waste classification model with government-led market and public participation. In order to explore the effectiveness of waste classification input in S city, this paper conducts analyses from the points of view of the classification facility’s construction, environmental effectiveness, social acceptability and operation sustainability, based on interviews with and questionnaire surveys completed by related parties. The results show that the current waste classification facility system in S city is basically completed; high rates of both properties and residents comply with the waste classification system. S city has established a government-led waste classification pattern that depends on social participation. This pattern has been recognized and accepted by residents and is economically sustainable. At the same time, it is pointed out that the current marginal effectiveness of the waste classification input is showing a declining trend. Future investment should shift from investment in facilities and equipment to incentives for autonomous management by residents, and the corresponding evaluation of investment and effectiveness should also change accordingly. This requires the government to guide the refined management system.